Finite element analysis of a triaxial test specimen - Abadies, Rosario Zamoras (1993)
This study was conducted to analyze the state of stress in a triaxial test specimen assumed as an elastoplastic material. The computer program developed was designed particularly to stimulate the effect of the rigid cap on the homogeneity of the state of stress in the specimen. The result indicated that despite the end restraints, a nearly homogenous state of stress still prevails away from the rigid cap provided the height to diameter ratio of the test specimen is at least two.